2016
DOI: 10.1111/psyp.12795
|View full text |Cite
|
Sign up to set email alerts
|

Trauma‐related dissociation: Psychological features and psychophysiological responses to script‐driven imagery in borderline personality disorder

Abstract: Defense reactions to threatening situations are vital adaptations to stress that protect organisms from injury and ensure survival. We retrospectively investigated the role of peritraumatic dissociation (PD) in the occurrence of severe psychopathology and dissociative patterns of reactions in borderline personality disorder (BPD). We recruited 28 patients with a clinical diagnosis of BPD and 15 healthy controls. The BPD group was divided according to the level of PD (low vs. high): BPD and PD (n = 15) and BPD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 50 publications
1
19
1
Order By: Relevance
“…After the experiment, some participants with current and remitted BPD spontaneously reported that they prepared themselves for the second experimental session, be it settling in anticipation of a stressful script or keeping relaxed in anticipation of a neutral script. This might have interfered with the induction of dissociation, as the scores we assessed were relatively low (increase of about 1.2 averaged sum score points in the DSS-4) compared to other studies (Bichescu-Burian et al, 2017;Krause-Utz et al, 2018;Ludäscher et al, 2010, with converted values of 1.5 and higher). The purposeful exclusion of traumatic events might account for the rather low scores in this study, while increasing the ecological validity of findings.…”
Section: Limitations and Perspectivecontrasting
confidence: 55%
See 1 more Smart Citation
“…After the experiment, some participants with current and remitted BPD spontaneously reported that they prepared themselves for the second experimental session, be it settling in anticipation of a stressful script or keeping relaxed in anticipation of a neutral script. This might have interfered with the induction of dissociation, as the scores we assessed were relatively low (increase of about 1.2 averaged sum score points in the DSS-4) compared to other studies (Bichescu-Burian et al, 2017;Krause-Utz et al, 2018;Ludäscher et al, 2010, with converted values of 1.5 and higher). The purposeful exclusion of traumatic events might account for the rather low scores in this study, while increasing the ecological validity of findings.…”
Section: Limitations and Perspectivecontrasting
confidence: 55%
“…Script‐driven imagery has been previously used to experimentally induce dissociation in cBPD patients (Barnow et al, 2012; Bichescu‐Burian, Steyer, Steinert, Grieb, & Tschoke, 2017; Krause‐Utz et al, 2018; Ludäscher et al, 2010; Winter et al, 2015). This approach has been shown to activate memories, which can be evaluated using affective self‐report measures and psychophysiological assessments (Bichescu‐Burian et al, 2017). Since mentally imagined interaction with a stimulus can induce similar emotional reactions as a real interaction with the same stimulus (Lang, 1979), our subjects were instructed to vividly imagine autobiographical events.…”
Section: Methodsmentioning
confidence: 99%
“…When BPD subjects are distinguished according to the level of Peritraumatic Dissociation (PD) based on the Peritraumatic Dissociative Experiences Scale, it appears that BPD with high PD (i) display the highest degrees of trauma exposure (ii) the most severe clinical symptoms, and (iii) a significant decrease in heart rate during stress elicitation. In contrast, an increase in heart rate was observed in the two other groups during stress elicitation (BDP with low PD and controls) ( Bichescu-Burian et al, 2016 ). Subjects with PTSD were also found to have a lower vagal tone (measured by HRV) at baseline than BPD; however, the comorbidity was not studied ( Meyer et al, 2016 ).…”
Section: Stress Reactivity In Bdpmentioning
confidence: 94%
“…Strictly connected to this biological aspect and the results regarding self-report levels of negative valance, the slow return to emotional baseline might be also attributed to the maladaptive effects of the rigid use of emotion regulation strategies (e.g., rumination, experiential avoidance). It was previously demonstrated that maladaptive emotion regulation affects both emotional subjective experience [41, 42] and long-term physiological responses [8184]. Eventually, this aspect could be heightened when BPD subjects are exposed to long-lasting emotional situations.…”
Section: Discussionmentioning
confidence: 99%